2012
DOI: 10.18553/jmcp.2012.18.7.527
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Frequency and Medication Adherence in Chronic Disease

Abstract: BACKGROUND: Prior research has shown a decrease in medication adherence as dosing frequency increases; however, meta-analyses have not been able to demonstrate a significant inverse relationship between dosing frequency and adherence when comparing twice-daily versus once-daily dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
273
0
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(309 citation statements)
references
References 61 publications
17
273
0
19
Order By: Relevance
“…In other study this information confirmed that lower adherence was associated with more prescribed medications [10], especially in users of diuretics and beta blockers, rarely in users of angiotensin -converting enzyme inhibitors (ACEI) and angiotensin II receptor blockers (ARB) [11], which was promoted by…”
Section: Discussionmentioning
confidence: 55%
“…In other study this information confirmed that lower adherence was associated with more prescribed medications [10], especially in users of diuretics and beta blockers, rarely in users of angiotensin -converting enzyme inhibitors (ACEI) and angiotensin II receptor blockers (ARB) [11], which was promoted by…”
Section: Discussionmentioning
confidence: 55%
“…A switch from a daily to a twice daily regimen was considered acceptable (i.e., a therapeutic alternative), but conversion to a 3 or more times a day drug was not considered acceptable due to the increased risk of nonadherence. [17][18][19] 4. For medications still remaining, the reviewer determined if the medication was a branded member of a class that is thought clinically to have class effect benefits and minimal risk of harm in switching (i.e., a therapeutic alternative).…”
Section: ■■ Methodsmentioning
confidence: 99%
“…Studies have demonstrated an inverse relationship between medication adherence and dosing frequency in patients with chronic diseases. Up to a 19% decrease in taking adherence, up to a 23% decrease in regimen adherence, and up to a 54% decrease in timing adherence in chronically ill patients whose treatment required them to take multiple daily doses compared to patients who are on once-daily regimens [62]. Similarly, researchers found that adherence was up to 12% higher in patients on a once-weekly dosing regimen compared to patients on more frequently dosed agents for the same conditions and up to 96% of patients preferred an intermittent dosing regimen [63].…”
Section: Igg-fc Fusion Therapeutics In a Real World Settingmentioning
confidence: 99%